Influencing climate change policy in Sri Lanka - European Initiative for Agricultural Research for Development (2013)
A partnership between IWMI, Sri Lankan Government agencies dates back to a national ‘Water for Food’ conference in 2009. After presenting research on the impacts of climate change on water resources and agriculture in Sri Lanka, the Institute was invited to attend workshops organised by the Ministry of Environment, provide information and comment on draft government reports. Through this collaboration, IWMI has made a significant contribution to the development of Sri Lanka’s climate change adaptation policies. IWMI research findings have been incorporated in the country’s Climate Change Adaptation Strategy 2011-2016 and Sri Lanka’s Second National Communication on Climate Change, which was submitted to the United Nations Framework Convention on Climate Change (UNFCCC) in 2011. IWMI’s findings are being used in a number of new projects, including a 2012 UNDP initiative aimed at building climate resilient activities into national household food security improvement and rural infrastructure programmes.